Transformative Leadership in Islamic Religious Education at Raudhatul Athfal: Advancing Competitive Islamic Management in Probolinggo, Indonesia - Devi Fitriah Islamiyah; Benny Prasetiya; Zohaib Hassan Sain (Journal of Islamic Education Research, 2024)
This study explores the transformational leadership strategies implemented by the principal of Raudhatul Athfal (RA) Nawa Kartika in Probolinggo, focusing on their impact on the quality of early childhood Islamic education. The method used is descriptive qualitative, examining the principal's approach to Islamic curriculum development, human resource management, facility improvement, and relationships with the community and parents. The results show that the principal's leadership, based on Islamic values and transformational leadership principles, has significantly improved the quality of education. The integration of Islamic values into the curriculum has shaped students' character and enhanced their cognitive development. Furthermore, continuous human resource management through teacher training and development has positively impacted the quality of teaching. Overall, the transformational leadership strategies applied by the principal of RA Nawa Kartika have proven effective in enhancing the quality of Islamic education. This study provides valuable insights for other educational institutions regarding the importance of visionary, inclusive leadership rooted in Islamic values in achieving educational goals, particularly in early childhood Islamic education.